2014
DOI: 10.1016/j.ymgme.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Human HOX gene disorders

Abstract: The Hox genes are an evolutionarily conserved family of genes, which encode a class of important transcription factors that function in numerous developmental processes. Following their initial discovery, a substantial amount of information has been gained regarding the roles Hox genes play in various physiologic and pathologic processes. These processes range from a central role in anterior-posterior patterning of the developing embryo to roles in oncogenesis that are yet to be fully elucidated. In vertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(110 citation statements)
references
References 112 publications
5
102
0
3
Order By: Relevance
“…Ichthyosaurs furnish the best-known exception: opthalmosaurians added digits anterior to digit one and posterior to digit five [196], whereas non-opthalmosaurians may have achieved polydactyly by interdigital or postaxial phalangeal bifurcation [197]. In most amniote groups, however, polydactyly is associated with a range of deleterious pleiotroipic effects [198][199][200], because limb development coincides with the phylotypic stage. Variation in this particular set of characters appears to be effectively locked down, therefore.…”
Section: Intrinsic Developmental Constraintsmentioning
confidence: 99%
“…Ichthyosaurs furnish the best-known exception: opthalmosaurians added digits anterior to digit one and posterior to digit five [196], whereas non-opthalmosaurians may have achieved polydactyly by interdigital or postaxial phalangeal bifurcation [197]. In most amniote groups, however, polydactyly is associated with a range of deleterious pleiotroipic effects [198][199][200], because limb development coincides with the phylotypic stage. Variation in this particular set of characters appears to be effectively locked down, therefore.…”
Section: Intrinsic Developmental Constraintsmentioning
confidence: 99%
“…Importantly, variation in Hox gene number, expression pattern and protein activity has played a major role in the evolution of the metazoan body plan (Gellon and McGinnis, 1998). Hox genes have also been associated with a number of human diseases (Quinonez and Innis, 2014), highlighting the fact that Hox proteins are key factors in development, evolution and physiopathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…These 39 genes are an evolutionary conserved family of genes that play a key role in the development of anteroposterior axis, but also in other physiologic and pathologic processes, such as oncogenesis [38,39]. Several experiments on chicks and mice have shown that Hox-gene mutations can lead to homeotic transformations [40].…”
Section: Discussionmentioning
confidence: 99%